Proximate and organoleptic analysis of cassava-based snack (combo bits) and chin-chin (2023)
This study investigated the proximate and organoleptic properties of combo bits and chin-chin. Specifically, it determined: proximate composition of combo bits and chin-chin, organoleptic properties of combo bits and chin-chin. Samples of combo bits and chin-chin were prepared using standard methods. One part of each product was subjected to proximate analysis while the other part was subjected to sensory evaluation. Proximate analysis of combo bits and chin-chin were carried out using standard methods. Twenty panelists were involved in sensory evaluation of both products. A 9-point hedonic scale was used to collect data on the sensory properties of combo bits and chin-chin. Data for sensory evaluation were analyzed using percentages (%). Findings indicate variations in the proximate analysis values (%) of combo bits and chin-chin. Also, combo bits was ranked higher when compared to chin-chin based on the 9-point hedonic scale rating for overall acceptability. Furthermore, none of the snacks was rated as being disliked (0%). There were however, variations in their ratings for “being liked”, ranging from, for instance, “liked moderately” in colour for combo bits (38.6%), “liked slightly” in colour for combo bits (20.5%), “liked very much” in colour for combo bits (30.1%); for chin-chin, “liked moderately” in colour for chin-chin (38.6%), “liked slightly” in colour for chin-chin (20.5%), “liked very much” in colour for chin-chin (19.3%). Based on findings two recommendations were made.